Adaptive Dynamics in Coordination Games - Crawford, Vincent P. (Econometrica, 1995)
This paper proposes a model of the process by which players learn to play repeated coordination games, with the goal of understanding the results of some recent experiments.In those experiments the dynamics of subjects' strategy choices and the resulting patterns of discrimination among equilibria varied systematically with the rule for determining payoffs and the size of the interacting groups, in ways that are not adequately explained by available methods of analysis.The model suggests a possible explanation by showing how the dispersion of subjects' beliefs interacts with the learning process to determine the probability distribution of its dynamics and limiting outcome.